Artificial Intelligence in Early Detection of Neurological Disorders - Hayat, Yawar; Khaja, Abdullah Mazharuddin; Rasool, Saad; Gill, Ahmed (International Journal of Innovative Research in Computer Science and Technology, 2025)
Because the start of neurological illnesses is sometimes subtle and gradual, early detection has always been a difficult task in the field of medical diagnostics. In addition to impeding prompt intervention, delayed diagnosis has a substantial negative influence on long-term results and patient quality of life. The development of artificial intelligence (AI) and machine learning (ML) in recent years has created revolutionary possibilities to raise the precision, effectiveness, and predictive capacity of neurological evaluations. This study offers a thorough analysis of the development, status, and prospects of AI-driven approaches in neurological diagnosis. We look at the creation of AI algorithms that can analyze massive clinical, genomic, and neuroimaging information and find patterns that are invisible to the human eye. Their use in the diagnosis of epilepsy, multiple sclerosis, Parkinson's disease, and Alzheimer's disease is specifically highlighted. These models exhibit improved capacities in disease classification, progression tracking, and early-stage identification.The study also discusses the incorporation of AI into healthcare workflows, showcasing both successful case studies and persistent issues such data heterogeneity, black-box model interpretability, and regulatory validation requirements. The significance of implementing AI in healthcare responsibly is emphasized by the ethical issues raised by algorithmic bias, data privacy, and patient permission.Lastly, we examine how AI might help neurology decision-making and tailored treatment, bringing in a new era of proactive care approaches and precision diagnostics.